Du Pont Analysis on the Financial Performance of PT Garuda Indonesia (Persero) Tbk - Abdul Latif; Fatimah Fatimah; Pebiola Pebiola; Erna Apriani; Akfika Rizky Sabilla (JOURNAL ECONOMICS AND STRATEGY, 2023)
Investors, companies, and the public assessing the performance of the company certainly look at the information instruments provided by the company in the financial statements in assessing the company's financial performance. PT Garuda Indonesia (Persero) Tbk is one of the State-Owned Enterprises (BUMN) engaged in aviation services in Indonesia; the condition and performance of the company have certainly been highly monitored by the government and other stakeholders, especially since this company in recent years has always experienced losses in its business operations so that it often injects funds from the government. This study aims to analyze the company's financial performance with Du Pont analysis techniques such as total assets turnover, net profit margin, equity multiplier, and return on equity for the 2020-2022 period. The analysis method used in this research is a descriptive quantitative analysis of the company's financial ratios with Du Pont analysis. The results showed that the Total Assets Turnover ratio in 2020, 2021, and 2022 was still below the industry average and was in poor condition. The Net Profit Margin ratio in 2020 and 2021 is below the industry average, negative with poor conditions, and 2022 above the industry average with good conditions. The Return On Investment ratio in 2020 and 2021 experienced a negative ratio with a conclusion of poor condition; in 2022, it improved with a positive ratio in good condition. The Equity Multiplier ratio in 2020, 2021, and 2022 needs to be in better condition, below standard, and hostile. The Return On Equity ratio in 2020, 2021, and 2022 needs to be in better condition. Keywords: Financial Performance, Financial Statements, Financial Ratios